EFEKTIVITAS ENDORPHINE MASSAGE TERHADAP TINGKAT KECEMASAN IBU BERSALIN PRIMIPARA - Sukmaningtyas, Wilis; Windiarti, Prahesti Anita (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
ABSTRACT: THE EFFECTIVENESS OF THE LEVEL OF ANXIETY ENDORPHIN MASSAGE MOM MATERNITY PRIMIPARA. Massage techniques to help mothers feel more refreshed, relaxed and comfortable during labor. It happened because the massage stimulates the body to release a compound endorphine which is a natural pain reliever. Endhorphine also can create a feeling of comfort and tasty reducing maternal anxiety felt. From the interviews conducted for 10 women giving birth were 6 pregnant women say afraid if something happens to the baby, and from 7 mothers who do massage say more prepared and calm in the face of labor. This study aims to determine the effectiveness of massage endorphin against maternal anxiety levels primiparaoleh family. This study was descriptive quantitative with cross sectional approach. Total population of 30 respondents, data were analyzed using univariate analysis. Result: The implementation endorphine massage performed by the respective families do and not do as many as 15 respondents (50%), the majority of respondents did not rate kecemasa do endorphine massage is as much as 7 respondents (45.7%) and the majority of respondents' level of anxiety endorphine massage is done lightly by 7 respondents (46.7%). Conclusion: respondent with massage endorphine mostly mild massage while respondents without endorphine mostly heavy. Â Keywords: anxiety, endorphine massage, maternity